Physico-chemical Properties of Poly(ethylene glycol)-block-polypeptide-graft-poly-(ethylene glycol) Film Improved by Poly(propylene glycol) - Zhu, Guo-Quan; Wang, Fa-Gang; Gao, Qiao-Chun; Liu, Yu-Ying (Asian Journal of Chemistry, 2013)
Poly(ethylene glycol)-block-poly(g-benzyl L-glutamate)-graft-poly(ethylene glycol)/poly(propylene glycol) (PEG-block-PBLG-graft-PEG/PPG) blend films were prepared by the solution casting method. Surface morphologies of the PEG-block-PBLG-graft-PEG/PPG blend films were studied by scanning electron microscopy and atomic force microscopy. Mechanical and chemical properties of the polymer blend films were investigated by tensile tests and surface contact angle tests. The results indicated that the introduction of PPG could obviously affect the properties of the polypeptide block-graft copolymer films.